2019
DOI: 10.1016/j.techfore.2018.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing university brand image and reputation through customer value co-creation behaviour

Abstract: Full bibliographic details must be given when referring to, or quoting from full items including the author's name, the title of the work, publication details where relevant (place, publisher, date), pagination, and for theses or dissertations the awarding institution, the degree type awarded, and the date of the award.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
147
5
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(171 citation statements)
references
References 105 publications
15
147
5
4
Order By: Relevance
“…This research contributes to filling literature than brand personality about the university, various marketing strategies that are out there today have been applied to a public company even college especially padjadjaran university which has moved to the form of college are legal entities, the time has come to apply a strategy branding for its institutions (Foroudi et al, 2019;Fazli et al, 2019;Schlesinger et al, 2017;Ng, 2019). Made high unpad brands that have a reputation.…”
Section: Introductionmentioning
confidence: 95%
“…This research contributes to filling literature than brand personality about the university, various marketing strategies that are out there today have been applied to a public company even college especially padjadjaran university which has moved to the form of college are legal entities, the time has come to apply a strategy branding for its institutions (Foroudi et al, 2019;Fazli et al, 2019;Schlesinger et al, 2017;Ng, 2019). Made high unpad brands that have a reputation.…”
Section: Introductionmentioning
confidence: 95%
“…Managing relationships with customers who are students, in the case of higher education, is fundamentally impacted by the competitiveness of the institution and its ability to respond flexibly to changes in the needs and expectations of students from the education process [10]. Another authors agree, and state that only an approach based on the active engagement of students in the creation of university education will enable their full satisfaction [11]. However, in connection with attracting customers (students), also emphasize the ever-increasing importance of marketing communication where interactive marketing communication tools mediated by the students' decision-making process have a major impact on the brand and image of the educational institution [4].…”
Section: Introductionmentioning
confidence: 99%
“…In the current stage of social development, a transition is taking place from quantitative to qualitative assessment of results [17] and students' satisfaction represents a key output variable for providing their services [22]. The results of recent studies prove that student satisfaction is an important tool of the relationship marketing and currently a fundamental tool of the personnel marketing of colleges and universities [11,20]. Educational institutions wishing to succeed in the specific conditions of a given country or at an international level must determine and evaluate the motivation, expectations, and needs of their students [19,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher education institutions can be competitive and provide better services or improve the existing ones only if they are continuously engaged in identifying students´ needs, preferences, and learning about the factors that affect their satisfaction (Prisacariu, 2015). To attract university students (customers), it is not enough to identify such students´ preferences when choosing a university, but universities must be able to react and adapt to their preferences (Foroudi et al, 2019;El-Hilali et al, 2015). It can be concluded that there is a growing pressure on university management to deal with and evaluate students´ preferences when they choose a university and to implement such findings in their strategic documents and personnel marketing.…”
Section: Introductionmentioning
confidence: 99%